Talents against all odds - Bahia, Sara (2011)
A mythical view of creativity which still prevails leads us to appreciate paintings produced by talented people with mental retardation within the context of an art for “outsiders” and arises a series of theoretical explanations that reinforce the belief that “idiot savants” can not be considered creative. However, “idiot savants” may be considered creative. Two research studies carried out in Portugal showed no significant differences between the evaluations of creative products painted by mentally retarded and renown artists in the answers of 358 psychologists and teachers of arts, economy, humanities and sciences to a specially designed questionnaire. These results are discussed as well as the factors that contribute to the development of artistic talents against all odds.